Enhancing opinion essay writing: successful global classroom session on transitional markers - Siti Ainun Jariyah, Hassan; Nurul Nadia, Muhammad (UMPSA, 2025)
PEKAN, 13 May 2025 - A successful Global Classroom (GC) session focusing on transitional markers in opinion essays was conducted via Google Meet. The GC session was organised by ULE1352 Essential English and ULE1310 Fundamentals of English Language courses and conducted by two instructors, Siti Ainun Jariyah Hassan and Nurul Nadia Muhammad. The session featured a special guest speaker, Ms. M.C. Dayani Siriwardana, an accomplished English Teacher from St.Mary's College, Kegalle, Sri Lanka. In addition, she also actively collaborates with international platforms such as Class2Class.org, Global Classroom, and AWTE Intellectual Exchange sessions.